THE FINANCIAL CRIME IN REPUBLIC OF MACEDONIA APSTRACT - Angeleski, Metodija; Stojanovski, Dusko; Nedelkovska, Martina; Kurtevska, Ivana; Gaberova, Nikolina; Miloseski, Dragan (European Scientific Journal, ESJ, 2014)
The economic crime as a system of groupings of types of criminal acts with similar characteristics in modern conditions is characterized by a rich and diverse criminal phenomenology, adaptable to all stadiums of the development of society. The financial crime is part of the economic crime which is rapidly evolving and expanding causing huge material damage, as that undermines the foundations of the functioning of any country, especially some that ten years ago transited from contract in a trading economy, what is case of the Republic of Macedonia. The article presents observations of the current situation with financial crime in the Republic of Macedonia, which highlight the specifics regarding the actions of all subjects included in the fight against this difficult and complex phenomenon. It’s rightfully to point out the need for specialized treatment of financial crime in managing financial investigations as well as criminal operating items. For this purpose are applied modern criminality tools and methods derived primarily from the bosom of conspiratorial police and judicial instruments and methods provided by the Law of the Financial Police. Resolved financial crime in the country is not a reflection of reality, given that this area is with extremely high “dark number”.